-9(7f-3)=19+8f

Simple and best practice solution for -9(7f-3)=19+8f equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(7f-3)=19+8f equation:


Simplifying
-9(7f + -3) = 19 + 8f

Reorder the terms:
-9(-3 + 7f) = 19 + 8f
(-3 * -9 + 7f * -9) = 19 + 8f
(27 + -63f) = 19 + 8f

Solving
27 + -63f = 19 + 8f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-8f' to each side of the equation.
27 + -63f + -8f = 19 + 8f + -8f

Combine like terms: -63f + -8f = -71f
27 + -71f = 19 + 8f + -8f

Combine like terms: 8f + -8f = 0
27 + -71f = 19 + 0
27 + -71f = 19

Add '-27' to each side of the equation.
27 + -27 + -71f = 19 + -27

Combine like terms: 27 + -27 = 0
0 + -71f = 19 + -27
-71f = 19 + -27

Combine like terms: 19 + -27 = -8
-71f = -8

Divide each side by '-71'.
f = 0.1126760563

Simplifying
f = 0.1126760563

See similar equations:

| 7+3z-4=7z+3-3z | | 2x+10+2x+10+4x=180 | | -33=8z+9z | | P/2=20 | | -3s-8s=-16 | | 23=3+2(h+9) | | 2x+10+2x+10+4x= | | 36+3(21-9)-1= | | -26+4n=9(2n-8) | | 5s^2-14s-3=3 | | 3/5(x) | | 4x=-12.36 | | -5p+(-3)=-4 | | 7x-14lnx=0 | | 2x+125+x+63=38 | | -4(2-5x)=35 | | x-14.4=7.02 | | (x=1)/3-x/4=1/2 | | -9+5(1+4k)=-29 | | -7+19-(-3)= | | 2.5b=9/5 | | x-90=(x-180)/5-10 | | -12.36/4= | | -9(5d-6)=-18 | | 10x-7=114 | | 12x-10=18x+10 | | -12.37/4 | | 2(b+6)=5 | | x-90=x/5-180/5-10 | | 2X-13=-47 | | -6+5(1+9s)=-24 | | x-90=x-180/5-10 |

Equations solver categories